Commune-level institutional arrangements and monitoring framework for integrated tree-based landscape management - Vu, T.P.; Nguyen, V.T.; Do, T.H. (World Agroforestry Centre, 2021)
Governance is a difficult task in the context of achieving landscape multifunctionality owing to the multiplicity of stakeholders, institutions, scale and ecosystem services: the ‘many-multiple’ (Cockburn et al 2018). Governing and managing the physical landscape and the actors in the landscape requires intensive knowledge and good planning systems. Land-use planning is a powerful instrument in landscape governance because it directly guides how actors will intervene in the physical landscape (land use) to gain commonly desired value. It is essential for sustaining rural landscapes and improving the livelihoods of rural communities (Bourgoin and Castella 2011, Bourgoin et al 2012, Rydin 1998), ensuring landscape multifunctionality (Nelson et al 2009, Reyers et al 2012) and enhancing efficiency in carbon sequestration, in particular (Bourgoin et al 2013, Cathcart et al 2007). It is also considered critical to the successful implementation of land-based climate mitigation, such as under Nationally Determined Contributions (NDCs), because the Land Use, Land-Use Change and Forestry (LULUCF) sector is included in the mitigation contributions of nearly 90 percent of countries in Sub-Saharan and Southern Asia countries and in the Latin American and Caribbean regions (FAO 2016).